Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada CV Pilar Perkasa Mandiri - Muhamad Agus Teguh Herlambang (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
The application of an effective work discipline leadership style in managing human resources in a company's performance. The purpose of this study was to determine the effect of leadership style on employee performance and the effect of work discipline on employee performance at CV.Pilar Perkasa Mandiri in Brebes Regency. The instrument of this study used a questionnaire. Samples were taken as many as 30 respondents from CV.Pilar Perkasa Mandiri Sejahtera, Brebes Regency. Data analysis and processing using SPSS. The results of this study indicate that leadership style has no effect on employee performance, while work discipline has an effect on employee performance